(untitled) (Educa Journal of Studies, 2026)
Inclusive education promotes equitable learning opportunities for all students, regardless of ability, background, or socio-economic status. This interdisciplinary study examines inclusive education practices in Swedish primary and secondary schools and their impact on social equity. Using surveys of 150 teachers, interviews with school administrators, and classroom observations, the research investigates strategies that facilitate inclusion and identify barriers to equity. Findings indicate that differentiated instruction, collaborative teaching, and policy-supported accommodations enhance inclusion and reduce disparities. Challenges include limited resources, insufficient teacher training, and systemic constraints. The study offers recommendations for policymakers and educators to strengthen inclusive education frameworks.